Veterinary Viewpoints, no. 1, 1989 - Cornell University. College of Veterinary Medicine; Redmond, Karen (Cornell University. College of Veterinary Medicine, 1989)
Topics in this issue include: Animal Welfare & the Veterinarian; Alumni Honor Dr. Roberts (Stephen J. Roberts); Pew Grant for Cornell: Veterinary Programs to be Studied; Dr. Saidla New Feline Extension Veterinarian (John E. Saidla); Calling the Small Animal Clinic?; Casper, the Polar Bear; Alumni Profile: Allan Prowten; Equine Projects Selected: Harry M. Zweig Equine Memorial Fund; Diagnostic Laboratory Offers Test for Lyme Disease (Metta Winter, Richard Jacobson, Sang Shin); Construction Plan Update: New Bonding Cap Signals Start; Author Honored: New York State Veterinary Medical Society Presents Bust to Dr. E. P. Leonard (Ellis P. Leonard).